Social-economic development of the united territorial communities and development of a strategy for sustainable development (case of Ukraine) - Белей (Belei), Cвітлана (Svitlana); Tarasenko, Denys; Тsyklaurі, Оlena; Rіabenka, Maryna; Mazurkevych, Iryna; Bashlai, Serhii (WSEAS, 2021)
The unification of territorial communities allows forming an effective and convenient system of management of the territory in which they live. However, the unification of territorial communities in Ukraine is uneven, which raises the question of why this is happening. The purpose of the study is to analyze the level of social-economic development of united territorial communities in Ukraine and the choice of sustainable development strategies (adaptation, innovation, anti-crisis) for UTCs of different levels, identify problems of social-economic development and outline areas to address them. Research methods: generalization and scientific abstraction; system-structural and comparative analysis; economic and mathematical modeling; clustering. It has been established that the unification of different territories in Ukraine took place unevenly (with different levels of social-economic development). The study found that the unification of different territories in Ukraine took place unevenly due to different levels of their socio-economic development. It has been established that throughout Ukraine, communities with a low and high level of development predominate and to a lesser extent with a medium level of development. According to the results of the analysis, territorial communities were grouped into 3 regional clusters: cluster 1 – UTCs and territories with a high level of socialeconomic development (Kyiv and 9 regions); cluster 2 – UTCs and territories with an average level of socialeconomic development (6 regions); cluster 3 – UTCs and territories with a low level of social-economic development (10 regions). It has been proved that the social-economic development of UTCs is ensured by the improvement of financial, innovative, and investment activities of enterprises operating in communities. It has been proposed to apply an adaptation strategy of sustainable development for the territories of cluster 1; for cluster 2 - innovative strategy of sustainable development; for cluster 3 - anti-crisis strategy of sustainable development. Continuation of research in terms of determining the impact of enterprises on the socio-economic development of UTCs is promising not only in scientific terms but also to address the applied problems of developing a strategy for sustainable development at the level of individual UTCs in Ukraine. The studied methodology for the unification of territorial communities can be used to predict the further formation of UTCs in Ukraine and can be applied for territorial and administrative reforms in countries with uneven regional development.
Keywords: Territorial Community (Commune, Community), United Territorial Communities (UTCs), Indicators of Social-economic Development, Welfare, Sustainable Development Strategy